2001
DOI: 10.1034/j.1600-079x.2001.300102.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and its analogs potentiate the nifedipine‐sensitive high‐voltage‐activated calcium current in the chick embryonic heart cells

Abstract: Effects of melatonin and its analogs on the voltage-activated calcium current of embryonic chick ventricular cardiomyocytes were investigated. Myocytes were dissociated from 14- to 16-day-old chicks (yellow Red Rob) embryonic hearts and cultured for 2 3 days. Calcium currents were studied by the patch-clamp technique. Whole-cell current recording showed nifedipine-sensitive, high-voltage-activated L-type calcium current inactivated in 70-100 ms during the voltage step period of 200 ms. There was no evidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…Several studies indicate that the effects of melatonin on calcium accumulation include a downstream influence on calcium influx through calcium channels (Ayar et al 2001;Mei et al 2001;Vanecek and Klein 1995). Our results suggest that in tectal cells, melatonin regulates calcium increases by an action involving an inhibitory Gprotein and GABA receptors.…”
Section: Melatonin's Effect On Calcium Levelssupporting
confidence: 50%
“…Several studies indicate that the effects of melatonin on calcium accumulation include a downstream influence on calcium influx through calcium channels (Ayar et al 2001;Mei et al 2001;Vanecek and Klein 1995). Our results suggest that in tectal cells, melatonin regulates calcium increases by an action involving an inhibitory Gprotein and GABA receptors.…”
Section: Melatonin's Effect On Calcium Levelssupporting
confidence: 50%
“…In this study we were interested whether the MT 2 ‐receptor is expressed in human coronary arteries and aorta, as it was repeatedly postulated that this receptor subtype is expressed and is functional in rat arteries [4, 8–10]. Furthermore, we also investigated the MT 2 expression in left ventricular specimens, because previous binding studies suggested that melatonin receptors are present in hearts of birds and other animals [11], and the ability of melatonin to modulate calcium channels of chick cardiomyocytes in vitro [12] suggests that this effect is also receptor‐mediated. A final aim of this project was to compare expression levels for the MT 2 receptor mRNA in healthy and diseased specimens (aorta, left ventricle and coronary arteria), which were derived from healthy heart donors or from patients with ischemic or dilated cardiomyopathy, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…proprioceptive systems, biomechanical factors, uncoupled neuro-osseous growth and dissociation between the timing of skeletal and CNS maturation [1][2][3][4][5][6][7]. There is considerable difficulty in distinguishing the primary underlying pathogenetic factor(s) that cause deformity from the secondary changes that arise secondary to the deformity.…”
Section: Introductionmentioning
confidence: 99%